POTENSI AGROWISATA SEBAGAI ALTERNATIF PARIWISATA BERKELANJUTAN - Witari, Made (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2009)
Agro-tourism is one of alternative tourism which can be implemented with a sustainable concept. It is potential tourism that can provide benefits in economic, socio-cultural, and environmental aspects which are already in accordance with the sustainable tourism goals. Agro-tourism activities emphasize on the quality of the environment, conservation and welfare improvement of the local community, especially farmers. It is expected that the community members are actively involved in agro-tourism development so as to increase their welfare and to ensure the continuity of agro-tourism activities in their area.